Всемирная история: в 24 т. / [А. Н. Бадак, И. Е. Войнич, Н. М. Волчёк и др.] - Бадак А. Н. (Современный литератор, 1999)
Экземпляры: ЦБ (2000 г.) / Инвентарный номер: 33372 / Цена: 28.00 / Авт.знак: В 84 / ГРНТИ: 03 / ББК: 63.3(0)